Mickiewicz alias Lenin: The Semantics of the Personage of the Vilnius Text - Lavrinec, Pavel (Respectus Philologicus, 2004)
The article examines semantics and function of the personage of the Vilnius text in one of its versions. The focus of the analysis are the texts devoted to Vilnius in Lithuanian, Polish, Byelorussian, and Russian languages predominantly written in verse and where the image of the poet of the past, prominent cultural worker, military man, and politician emerges as an important characteristic of the town locus. Usually such personage of the past is related to a historical or biographical episode of Vilnius. Moreover, his image and the episodes are implied or introduced by the expanded thematic motif in connection with concrete toponyms, famous buildings, and monuments. Thus, cultural, religious, and ideological tradition, that the subject of the text identifies himself with, is introduced. At the same time this personage indicates the precedent, reproduced in the present or which is subject to reproduction in the future. The study reveals the precedence as the fundamental characteristic of Vilnius locus - it is open to the future of eternal returns to the initial intensity of existence and renewal of involvements in the supreme values.
Keywords: Byelorussian culture; communism; Lithuanian poetry; locus; myth; national revival